ABDULLA QAHHOR IJODIDA KICHIK JANRLAR POETIKASI VA UNING O’ZIGA XOSLIGI (Archive of Conferences, 2022)
In this article, it is stated that the dealing with the poetics of small genres in the works of the writer Abdulla Qahhor, his individual skills and peculiarity.